The Effects of Racial/Ethnic Minority Status on Sleep, Mood Disturbance, and Depression in People with Fibromyalgia - Marr NC; Van Liew C; Carovich TF; Cecchini GA; McKinley LE; Cronan TA (Psychology Research and Behavior Management, 2020)
Nicole C Marr,1 Charles Van Liew,2 Tessa F Carovich,1 Gianna A Cecchini,1 Lauren E McKinley,3 Terry A Cronan1 1Department of Psychology, San Diego State University, San Diego, CA, USA; 2School of Nutrition and Health Promotion, Arizona State University, Tempe, AZ, USA; 3Department of Psychological Sciences, University of California, Merced, CA, USACorrespondence: Terry A Cronan Tel +1 619 594 4595Fax +1 619 594 1247Email tcronan@sdsu.eduPurpose: Fibromyalgia syndrome (FMS) is a chronic musculoskeletal pain disorder that is characterized by persistent and widespread pain. FMS has been associated with sleep disturbance, mood disorders and depression. Racial/ethnic minorities are less likely to receive a diagnosis of FMS than White individuals. Although mood disorders and depression are prevalent among racial/ethnic minority groups, researchers have not examined whether there are differences between racial/ethnic minorities and White individuals with FMS.Participants and Methods: The participants were 600 people who were 18 years of age or older and who had a physician’s diagnosis of FMS, which was confirmed using the 1990 American College of Rheumatology criteria. Most participants were female (95.5%) and White (85.0%). Sleep disturbance was assessed using the Pittsburgh Sleep Quality Index (PSQI), mood disturbance was assessed using the Profile of Mood States (POMS), and depression was assessed via the Center for Epidemiological Studies Depression Scale (CES-D).Results: Racial/ethnic minorities reported significantly greater levels of sleep disturbance, significantly greater levels of mood disturbance, and had significantly greater levels of depression than White participants. However, racial/ethnic minorities had significantly greater reductions in mood disturbance over the one-year period than White participants.Conclusion: Overall, the findings from the present study indicated that racial/ethnic minorities had “worse” physical and psychological outcomes than White participants.Keywords: chronic illness, pain, health disparities, psychosocial impact